Transitivity Process in Sia’s Selected Songs Lyrics - Dini Riandini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The focus of this research is to find the usage of the transitivity processes in SIA’s selected song lyrics. This research is descriptive qualitative research. This study attempts to identify and investigate transitivity mechanisms that are employed in the SIA’s selected song lyrics. The source data of this research are the five selected song lyrics of SIA. Meanwhile, the data of this research are the clauses that used transitivity processes in SIA’s selected song lyrics. The interactive model is used to analyze the research's data. The results show that five of SIA’s song lyrics contain all six categories of transitivity processes, which include mental, relational, material, verbal, behavioral, and existential processes. From the six types of transitivity processes that are found, the material process is dominantly used in SIA’s selected song lyrics. It suggests a connection between the physical activity that occurs in the social phenomenon and the lyrics of the songs chosen by SIA. In order to fully comprehend the song's meaning, readers should be aware of transitivity processes. Along with that, it also benefits the songwriter by giving them more freedom to craft lyrics with a variety of language.